2007
DOI: 10.1016/j.bodyim.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of body perceptions in relation to measured body composition in young Japanese males and females

Abstract: The body composition of 139 Japanese females and 84 Japanese males (aged 18-30 years) was measured using anthropometry to assess gender differences in body perceptions in relation to their measured values. Participants were asked to rate perceptions of their own "heaviness" and "fatness" and these were compared to their BMI and percent body fat (%BF). Japanese females showed a significantly greater desire to lose body weight (-4.20+/-0.6 kg) compared to males (0.27+/-1.4 kg). Females also showed poor understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
19
1
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 35 publications
5
19
1
8
Order By: Relevance
“…Moreover, under-reporting was also independently associated with perceiving one's weight as too light. This may be due to the excessive weight concerns and strong desire for thinness commonly observed in young Japanese women, irrespective of actual weight status (19,20). A similar independent infl uence of both actual weight status and perceived weight consciousness on underreporting has been observed in other obese populations (10,14).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, under-reporting was also independently associated with perceiving one's weight as too light. This may be due to the excessive weight concerns and strong desire for thinness commonly observed in young Japanese women, irrespective of actual weight status (19,20). A similar independent infl uence of both actual weight status and perceived weight consciousness on underreporting has been observed in other obese populations (10,14).…”
Section: Discussionmentioning
confidence: 69%
“…A characteristic of young Japanese women is their relatively low BMI, which is nevertheless accompanied by excessive weight concerns and a strong desire for thinness (19,20), a combination seldom observed in other countries. In particular, we investigated the hypothesis whether actual and perceived weight statuses were independently associated with energy intake misreporting in this unique population.…”
mentioning
confidence: 99%
“…We cannot rule out the possibility that the association between rate of eating and overweight observed here was the result of post hoc changes in dietary behavior (in a healthier direction) as a consequence of overweight. This may be particularly relevant in female populations, given the excessive weight concerns observed in young Japanese women (24,25). These concerns may explain why the association was relatively weak in female adolescents.…”
Section: Discussionmentioning
confidence: 98%
“…29 A study carried out in Japan on body perceptions found that women had a poor understanding of their heaviness/fatness in relation to their actual body weight. 30 Even though, or especially because, the general population have such misperceptions about their weight (either overweight or underweight), it is vital that HCW accurately perceive their own weight status in order to be able to perform their roles in health care better.…”
Section: Discussionmentioning
confidence: 99%